Domino decarboxylative arylation and c-o selective bond formation toward chromeno(2,3-b)pyridine-2-one skeletons - Ahadi, Elmira Meghrazi; Abbasi Kejani, Alireza; Khosravi, Hormoz; Fathi Vavsari, Vaezeh; Balalaie, Saeed; Rominger, Frank; Bijanzadeh, Hamid Reza (The journal of organic chemistry, 2021)
Practical Pd-catalyzed 2-pyridones were designed to achieve chromeno(2,3-b)pyridine-2-ones. The reaction proceeds through domino nucleophilic addition and decarboxylative arylation, respectively. This methodology offers a moderately efficient approach to construct the bioactive, fused-heterocyclic skeletons via selective C-O bond formation and decarboxylative arylation in a single step with high selectivity and good yields.
Gesehen am 01.02.2022